Fis is essential for capsule production in Pasteurella multocida and regulates expression of other important virulence factors. - Jason A Steen (Public Library of Science (PLoS), 2010)
P. multocida is the causative agent of a wide range of diseases of animals, including fowl cholera in poultry and wild birds. Fowl cholera isolates of P. multocida generally express a capsular polysaccharide composed of hyaluronic acid. There have been reports of spontaneous capsule loss in P. multocida, but the mechanism by which this occurs has not been determined. In this study, we identified three independent strains that had spontaneously lost the ability to produce capsular polysaccharide. Quantitative RT-PCR showed that these strains had significantly reduced transcription of the capsule biosynthetic genes, but DNA sequence analysis identified no mutations within the capsule biosynthetic locus. However, whole-genome sequencing of paired capsulated and acapsular strains identified a single point mutation within the fis gene in the acapsular strain. Sequencing of fis from two independently derived spontaneous acapsular strains showed that each contained a mutation within fis. Complementation of these strains with an intact copy of fis, predicted to encode a transcriptional regulator, returned capsule expression to all strains. Therefore, expression of a functional Fis protein is essential for capsule expression in P. multocida. DNA microarray analysis of one of the spontaneous fis mutants identified approximately 30 genes as down-regulated in the mutant, including pfhB_2, which encodes a filamentous hemagglutinin, a known P. multocida virulence factor, and plpE, which encodes the cross protective surface antigen PlpE. Therefore these experiments define for the first time a mechanism for spontaneous capsule loss in P. multocida and identify Fis as a critical regulator of capsule expression. Furthermore, Fis is involved in the regulation of a range of other P. multocida genes including important virulence factors.